NILAI-NILAI SOSIAL DALAM NOVEL TING! KARYA PRIYANTO CHANG: PENDEKATAN SOSIOLOGI SASTRA - Indah Purnama Sari; Nurhayati Harahap (IKIP Siliwangi, 2023)
In a literary work such as a novel, of course there are social values in social life. These values in social life develop into social values that require sociological studies such as in a literary work in the form of a novel entitled